2009
DOI: 10.1016/j.otohns.2008.12.047
|View full text |Cite
|
Sign up to set email alerts
|

The value of neurostimulation and intraoperative nerve monitoring of inferior laryngeal nerve in thyroid surgery

Abstract: Our results indicate that NSLP is a safe and reliable intraoperative method of RLN monitoring. Moreover our data confirm that IONM is not a helpful tool to reduce the rate of palsy in thyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 15 publications
4
42
0
1
Order By: Relevance
“…Several studies show a small reduction in RLNP incidence using IONM, but fail to exhibit statistical significance when compared with direct visualization alone. 6,12,13,17,[49][50][51][52][53][54] The one published randomized control trial comparing IONM versus identification alone in bilateral thyroid surgery concluded that IONM reduced rates of transient but not permanent palsies. 55 The recent meta-analysis by Higgins et al analysed 56 There are some instances where evidence for IONM use is stronger, suggesting that it can aid in the identification of the nerve, correlating with decreased complication rates.…”
Section: The Role Of Ionmmentioning
confidence: 99%
“…Several studies show a small reduction in RLNP incidence using IONM, but fail to exhibit statistical significance when compared with direct visualization alone. 6,12,13,17,[49][50][51][52][53][54] The one published randomized control trial comparing IONM versus identification alone in bilateral thyroid surgery concluded that IONM reduced rates of transient but not permanent palsies. 55 The recent meta-analysis by Higgins et al analysed 56 There are some instances where evidence for IONM use is stronger, suggesting that it can aid in the identification of the nerve, correlating with decreased complication rates.…”
Section: The Role Of Ionmmentioning
confidence: 99%
“…Numerous studies have been published regarding the potential benefits and limitations of RLN neuromonitoring 13-18. The largest non-randomized study of RLN neuromonitoring in thyroid surgery did not show a statistically significant difference in the incidence of RLN injury as a function of neuromonitoring 14.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Intraoperative neuromonitoring can also help to predict and prognosticate the degree of RLN nerve injury. [14][15][16][17] Previous studies of normative EMG data have been done in American and European populations. [18][19][20] Hopefully, by defining the normative RLN monitoring parameters, we can predict the degree of nerve injury following which nerve monitoring signals may be altered or lost.…”
Section: Role Of Intraoperative Neuromonitoringmentioning
confidence: 99%